Pengembangan Aplikasi Reado: Aplikasi Pembelajaran Bahasa Inggris Bagi Anak Pada Kegiatan Sosial Komunitas Katalis Pendidikan dengan Metode Design Sprint - Rachmalia Dewi; Agi Putra Kharisma; Candra Dewi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Indonesia is a country listed at the 61st position of 100 countries in the world based on an English proficiency index value of 50.06 that is below the average value of 53 and Indonesia is placed in the low category. This is because English learning is currently not going well. English learning can be done by using teaching strategy which is learning through educational games using electronic devices for learning words in English. In addition, statistical data show that the majority of the public is using an Android-based mobile application. Therefore in this research, the development of educational game for children through Android-based mobile devices is called Reado application. The development of this application was carried out by using the design sprint method that were tested on children from the social activities of the Katalis Pendidikan Community which consisted of 22 children. From the application of the design sprint method, based on the result of the black box testing that is 10 tests of the functional requirements have passed and have been verified, so it is stated that the Reado application has fulfill user's specific needs. In addition, based on the results of usability testing from grades 1 to 6, the results obtained that the value of the efficiency aspect has an average of 93.5% which is